The Indicative of Grace & The Imperative of Freedom: An Invitation to the Theology of Eberhard Jüngel - Nelson, Derek (Dialog, 2005)
This essay offers a comprehensive introduction to German theologian Eberhard Jüngel's theology and philosophy of religion. It traces his intellectual development, beginning with his formation studies in New Testament with Ernst Fuchs, and ends with his controversial position in matters of church unity and ecumenism. Special attention is paid to his theological anthropology, and the potential contributions his theology could make in the North American context are assessed.